Council of Europe. European Commission against Racism and Intolerance: Recommendations on Media and Internet in New Country Reports - McGonagle, T. (2012)
On 21 February 2012, the European Commission against Racism and Intolerance (ECRI) released its latest reports on Iceland, Italy, Latvia, Luxembourg, Montenegro and Ukraine, adopted in the fourth cycle of its monitoring of the laws, policies and practices to combat racism in the Member States of the Council of Europe. With the exception of the Report on Montenegro, all of these reports contain sections focusing specifically on the media/Internet.